Diaspora and displacement in the fiction of Abdulrazak Gurnah - Ajulu-Okungu, Anne (My University, 2007)
This study examines the effects of diaspora and displacement in characters as presented in Abdulrazak Gurnah’s Paradise, Admiring Silence and By the Sea. It looks at the role played by these effects in the construction of ideas of home and identity in the characters. Displacement is studied here against a backdrop of a long history of movements brought about by trading activities, exile and voluntary migrations. The texts are set in the east African coastal region, the islands and in Western countries such as England. The study relies on theories of postcolonialism and diaspora for its reading. The introduction places Gurnah’s work within the postcolonial archive by looking at his stance against the existing postcolonial discourses. It is also of importance to consider Gurnah’s biography and attempt to relate this to the view he takes as he narrates this geographical space in a postcolonial era. Chapter two looks at ideas of home as posited by different theorists in relation to the displaced and scattered characters he presents in these texts. Chapter three is concerned with how characters construct their identities against the ideas of ‘otherness’. In this chapter, I argue that Gurnah’s ideas of ‘otherness’ operate outside the (post)colonial idea of the same where the other is defined purely by difference in race. In chapter four I examine the significance of the preponderance of violence in the families presented by Gurnah. I investigate the connection between this perpetration of violence in the family and the idea of an elusive ‘paradise’ which runs through all Gurnah’s texts. The conclusion summarizes my major findings about Gurnah’s presentation of diaspora and displacement in the East African coast and the islands, and how he uses different structures like the home, self and the family to do this.
Student Number : 0515393R - MA research report - School of Literature and Language Studies - Faculty of Humanities
Keywords: Abdulrazak Gurnah; displacement; diaspora; otherness; home; violence; East African Literature; postcolonialism; family